Relationships between predatory aquatic insects and mosquito larvae in residential areas in northern Thailand - Nattawut Sareein (2020)
© 2019 The Society for Vector Ecology In order to elucidate the poorly understood relationships between mosquito larvae and their predatory aquatic insects in urban and suburban areas of tropical Southeast Asia, where vector-borne diseases are prevalent, aquatic insects were sampled from 14 aquatic habitats in residential areas of Chiang Mai, northern Thailand, during the rainy season (July to November) in 2016. Correlations among biological variables, densities of major predatory aquatic insect groups (i.e., Odonata, Coleoptera, and Hemiptera: OCH group) in wetlands and artificial lentic habitats, and the density of mosquito larvae were analyzed. Among the sampled mosquito larvae, Culex spp. were the most abundant, and both OCH density and water quality were major determinants of Culex spp. density (rs = −0.302 and −0.396, respectively). Logistic regression analyses indicated that the probability of Culex spp. occurrence was significantly and negatively correlated with OCH density. Furthermore, high macrophyte abundance was associated with higher predator density, potentially reducing mosquito density. Hemipteran predators were most negatively correlated with Culex spp. density, regardless of whether macrophyte abundance was high or low (rs = −0.547 and −0.533, respectively). Therefore, hemipteran predators were the most important aquatic insect predators in the urban and suburban residential areas of Chiang Mai, Thailand, and OCH species, such as the hemipteran Micronecta scutellaris, could be used as biological control agents against mosquitoes in the region.